Internet of things (IoT): a survey on protocols and security risks - Aswathy, R H; Malarvizhi, N (International Journal of Engineering and Technology, 2018)
A dramatic change by the growth of new ubiquitous computing, our globe is moving towards the fully connected paradigm called Internet of Things (IoT). The world is being connected and interlinked with the exponential growth of this pervasive technology. It plays a significant role in many fields such as healthcare, manufacturing industry, agriculture, transportation, smart homes etc and reinforces our everyday life. It acts as an aegis for covering all the factors such as protocols, key elements, technologies etc. IoT includes many capabilities and numerous mechanisms but protection hassle that slow down the era. In this paper we discussed about essential protocols and security issues of IoT.